Clinical significance of variants of J-points and J-waves: early repolarization patterns and risk - Junttila, M Juhani; Sager, Solomon J; Tikkanen, Jani T; Anttonen, Olli; Huikuri, Heikki V; Myerburg, Robert J (European heart journal, 2012)
The variations in the electrocardiographic patterns of J-point elevations, and the complex of J-points and J-waves in early repolarization (ER), in conjunction with disparities in associated sudden cardiac death (SCD) risk, have lead to a recognition of the need to carefully classify the spectrum of these observations. Many questions about the pathogenesis of J-wave patterns, and the associated magnitudes of risk, remain unanswered, especially in regard to the risk implications in certain high-prevalence subpopulations such as athletes, children, and adolescents. Interest in these electrocardiography (ECG) patterns has grown dramatically in recent years, in large part because of the frequency with which these patterns are observed on routine ECGs. In this review, we discuss the current knowledge on the prevalence of different J-point/J-wave patterns and estimates of the magnitude of mortality and SCD risk associated with J-point elevations and J-waves, in what has become known as ER patterns.